Depressive symptoms are independently associated with cirrhosis in untreated subjects with Chronic Hepatitis C infection (Research, Society and Development, 2020)
Objectives: Depression has shown to be a major public health problem, and is often reported in people with chronic hepatitis C infection. However, little is known about the role of liver fibrosis in predicting depressive symptoms among untreated patients. This study aimed to assess depressive symptoms among HCV-untreated patients, and to explore its association with liver fibrosis. Methods: A propensity score matched cross-sectional study was conducted on 154 subjects with CHC infection. Depression was defined as a score greater than 11 points to depression symptomatology in the Beck Depression Inventory-II. Results: The prevalence of depressive symptoms was 42.9%, and affected predominantly females, aged ≥ 45 years, who had an overall lower education level, without a history of current or previous use of antidepressants or anxiolytics. Median BDI-II score was 6 (IQR, 3 – 16) and 12 (IQR, 6 – 19) for the non-cirrhotic and cirrhotic group, respectively. Depressive symptoms were more frequent in compensated cirrhotic subjects than non-cirrhotic subjects, despite controlling for a range of demographic variables and comorbid conditions. Conclusions: HCV-untreated subjects have an elevated prevalence of depressive symptoms. This is especially relevant among those with cirrhosis, and should raise the awareness of this condition to health professionals.